Draft genome analysis for Enterobacter kobei, a promising lead bioremediation bacterium - El-Beltagi, Hossam S.; Halema, Asmaa A.; Almutairi, Zainab M.; Almutairi, Hayfa Habes; Elarabi, Nagwa I.; Abdelhadi, Abdelhadi A.; Henawy, Ahmed R.; Abdelhaleem, Heba A. R. (Frontiers in Bioengineering and Biotechnology, 2024)
Lead pollution of the environment poses a major global threat to the ecosystem. Bacterial bioremediation offers a promising alternative to traditional methods for removing these pollutants, that are often hindered by various limitations. Our research focused on isolating lead-resistant bacteria from industrial wastewater generated by heavily lead-containing industries. Eight lead-resistant strains were successfully isolated, and subsequently identified through molecular analysis. Among these, Enterobacter kobei FACU6 emerged as a particularly promising candidate, demonstrating an efficient lead removal rate of 83.4% and a remarkable lead absorption capacity of 571.9 mg/g dry weight. Furthermore, E. kobei FACU6 displayed a remarkable a maximum tolerance concentration (MTC) for lead reaching 3,000 mg/L. To further investigate the morphological changes in E. kobei FACU6 in response to lead exposure, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were employed. These analyses revealed significant lead adsorption and intracellular accumulation in treated bacteria in contrast to the control bacterium. Whole-genome sequencing was performed to gain deeper insights into E. kobei’s lead resistance mechanisms. Structural annotation revealed a genome size of 4,856,454 bp, with a G + C content of 55.06%. The genome encodes 4,655 coding sequences (CDS), 75 tRNA genes, and 4 rRNA genes. Notably, genes associated with heavy metal resistance and their corresponding regulatory elements were identified within the genome. Furthermore, the expression levels of four specific heavy metal resistance genes were evaluated. Our findings revealed a statistically significant upregulation in gene expression under specific environmental conditions, including pH 7, temperature of 30°C, and high concentrations of heavy metals. The outstanding potential of E. kobei FACU6 as a source of diverse genes related to heavy metal resistance and plant growth promotion makes it a valuable candidate for developing safe and effective strategies for heavy metal disposal.